Tariffs versus VAT in the presence of heterogeneous firms and an informal sector - Ronald B. Davies; Lourenço Paz (University College Dublin, UCD School of Economics, 2010)
The debate over the use of tariffs or value added taxes in developing countries has focused on the difficulty of collecting VAT from the informal sector of the economy. This paper contributes by considering this issue with heterogeneous firms and endogenous entry. This yields two new results. First, a cut in the tariff in and of itself can reduce the size of the informal sector. Second, the imposition of a VAT need not increase the number of informal firms. In fact, for many parameterizations of the model, higher VAT reduces informality. Despite this, whether a revenue neutral shift from tariffs to VAT increases or decreases welfare depends on the parametrization. Therefore while this move may be welfare improving in some cases, it is not a one-size fits all policy.
hdl:10197/2641
Keywords: 330